Clinical characteristics and lateralization of the horizontal semicircular canal light cupula - Qin, Wenjing; Liu, Zheng; Zhu, Yanhan; Zhang, Xueyan; Xu, Jiao; Zhou, Tao; Wei, Lingli; Fang, Yi; Chang, Liying (Frontiers in Neurology, 2024)
Introduction: Despite the clinical utility of supine roll test (SRT) and null point (NP) in diagnosing light cupula, there exists a notable gap in the literature concerning the comprehensive evaluation of lateralization values based on nystagmus characteristics and the intensity of direction-changing positional nystagmus (DCPN) in the SRT. Additionally, limited data on canal paresis (CP) underscores the need for further research to elucidate this mechanism. This study aims to investigate the characteristics of nystagmus and lateralization of light cupula. Methods: Eighty-five patients (68 females; mean age, 60.9 years) with light cupula were reviewed. We summarized the characteristics of spontaneous nystagmus, supine positioning nystagmus, bow nystagmus, and lean nystagmus. Then, the side of the NP was identified as the affected side, and the values of the fast phase direction of spontaneous nystagmus, supine positioning nystagmus, bow nystagmus, and lean nystagmus, as well as the intensity of the DCPN in the SRT, were used to diagnose the affected sides. Caloric testing was also performed for some patients. Results: The frequencies of supine positioning nystagmus, bow nystagmus, and lean nystagmus were higher than spontaneous nystagmus (p<0.001). The second NP and third NP were readily detected, affecting the left and right sides in 38 and 47 patients, respectively. Lateralization through the fast phase directions of bow and lean nystagmus did not significantly differ from that of NP (all p>0.05). However, the accuracy rate of lateralization through the sides with more vigorous DCPN in the SRT was 63.5%, significantly lower than through NP (p<0.001). Particularly in patients with supine positioning nystagmus, the rate was only 58.7% (p<0.001). Among the 70 patients who underwent caloric testing, 37 had abnormal CP, and the sides of the reduced caloric reaction were ipsilateral to the affected sides of light cupula in 83.8%. Conclusions: Besides utilizing the NP to determine the affected side, the fast phase direction of the bow nystagmus or lean nystagmus can also aid in identification. However, a simple comparison of the intensity of DCPN in SRT cannot provide accurate lateralization. There is a high incidence of CP on the affected side of light cupula.